DENISOVA CAVE: A PROMINENT PALEOLITHIC SITE IN NORTH ASIA - Aboualhassan BAKRY (Fayoum University, 2017)
Denisova Cave is situated in the Altai region of Siberia (Russia). It contains more than twenty layers of excavated artifacts indicative hominin occupation dating as far back as 280,000 years BP and as recent as the Middle Ages. The archaeological materials from the Pleistocene deposits are some of the most important sources of information regarding the Paleolithic age in Northern Asia. In the Pleistocene layers of the cave a finger bone (2008) was unearthed within stratum 11 belonging to a six or seven year-old unknown hominin girl that dates back roughly between 48,000 and 30,000 years. Later it was established that this bone belonged to a human whose mitochondrial DNA is distinct from the DNA of Neanderthals and anatomically modern humans; it belongs to a new kind of hominins called Homo sapiens altaiensis – “Denisovans”. This paper aims to shed more light on the analysis of the materials discovered within the Pleistocene layers of the cave (lithis tools, faunal, and human remains), demonstrating how multidisciplinary research and applying the scientific method in analysing a single site could reveal such unexpected, previously unknown facts, thus casting a new light on Paleolithic life in this region of North Asia.